Measuring Prosocial Behaviors: Psychometric Properties and Cross-National Validation of the Prosociality Scale in Five Countries - Luengo Kanacri, Bernadette Paula; Eisenberg, Nancy; Tramontano, Carlo; Zuffiano, Antonio; Caprara, Maria Giovanna; Regner, Evangelina; Zhu, Liqi; Pastorelli, Concetta; Caprara, Gian Vittorio (Frontiers in Psychology, 2021)
This research investigated the psychometric properties of the Prosociality Scale and its cross-cultural validation and generalizability across five different western and non-western countries (China, Chile, Italy, Spain, and the U.S.). The scale was designed to measure individual differences in a global tendency to behave in prosocial ways during late adolescence and adulthood. Study 1 was designed to identify the best factorial structure of the Prosociality Scale and Study 2 tested the model’s equivalence across five countries (N = 1.630 young adults coming from China, Chile, Italy, Spain and the U.S.; general Mage = 21.34; SD = 3.34). Findings supported a bifactor model in which prosocial responding was characterized by a general latent factor (i.e., prosociality) and two other specific factors (prosocial actions and prosocial feelings). New evidence of construct validity of the Prosociality Scale was provided.